The Changing Transition to Adulthood : Leaving and Returning Home. - Goldscheider, Francis (Understanding families., 1999)
This book examines the reasons why children ultimately leave home to live on their own and how the pattern has changed throughout the 20th century. The authors make use of data from the National Survey of Families and Households to: construct patterns for when children leave home; and establish the most important criteria for leaving home amongst different groups in the United States - men, women, blacks, hispanics, whites, and different religious groups and social classes.